Effect of plasma glucose at admission on COVID-19 mortality: experience from a tertiary hospital. Issue 6 (8th June 2021) - Kumar, Bharat; Mittal, Madhukar; Gopalakrishnan, Maya; Garg, Mahendra K; Misra, Sanjeev
Abstract : Objective: Plasma glucose has been correlated with in-hospital mortality among many diseases including infections. We aimed to study the plasma glucose at the admission of hospitalized patients with COVID-19 at a tertiary care referral hospital at Jodhpur, India and its relation with mortality. Design: A hospital-based clinical study of plasma glucose of COVID-19 patients conducted from May 15 to June 30, 2020 after ethical approval. Measurements: Random blood samples at admission were collected for plasma glucose, interleukin-6 (IL6) and high sensitivity C-reactive protein (hsCRP) after written informed consent was obtained. Plasma glucose was analyzed by the automated analyzer, IL6 by chemiluminescent immunoassay and hsCRP by immune-turbidimetric assay. Results: A total of 386 patients were studied (female 39.6%); 11.1% had severe disease and 4.1% expired. There were 67 (17.4%) patients with known diabetes mellitus (DM). Patients with a history of DM had three times higher mortality (6/67, 9%) than those without DM (10/309, 3.1%). Patients with moderate and severe disease according to ICMR and WHO grading had higher plasma glucose than those with asymptomatic or mild disease ( P < 0.0001). Plasma glucose levels at admission were significantly higher in non-survivors when compared to those who survived (297 ± 117 vs 131 ± 73; P < 0.0001). COVID-19 patients showed increased mortality with incremental plasma glucose levels. The hazard ratio for mortality was 1.128 (95% CI 0.86–14.860), 1.883 (95% CI 0.209–16.970), and 4.005 (95% CI 0.503–32.677) in random plasma glucose group of >100–200, >200–300 and >300 mg/dL, respectively, compared to those with random plasma glucose of <100 mg/dL at admission. Plasma glucose was strongly correlated with hsCRP ( P < 0.001) and IL6 ( P < 0.0001). Conclusions: Plasma glucose at admission in hospitalized COVID-19 patients is a strong predictor of mortality.